Implementation and Evaluation of Large Rsa Encryption and Decryption Keys For Internet Security - H. Belgassem, Seddeq (2004)
The Internet is a powerful tool in today's ever-growing society. Computer Information and Internet security has recently become a popular subject due to the explosive growth of the Internet and the migration of commerce practices to the electronic medium. We use the Internet for many things, such as research, banking, and commercial sales. In each of this business, their needs to be save haven for which security is not compromised while companies run its business online. Thus the authenticity and privacy of the information transmitted and the data received on networked computers is of utmost importance. The deployment of network security procedures requires the implementation of Cryptographic algorithms. To facilitate this security issue, it is best to define a problem and advice a solution. The problem is computer crime via hackers,crackers, and thieves. The solution is to apply a security system upon the online system. The Science of cryptography provides one means to combat these attacks. These include encryption, decryption, authentication, and digital signature. Performance has always been the most critical characteristic of a cryptographic algorithm, which determines its effectiveness. In this research the most popular and used algorithm, which is RSA, is implemented with a new modification in order to reduce the calculation time of the algorithm. A large encryption and decryption key sizes ranging from 1024 bit to 3072 bit have been generated and used in order to provide a high level of security. The computation results show that the key generation process using the modified algorithm is around three times faster than the old implementation. Both old and new implementations are used to encrypt and decrypt different sizes and types of files using different generated key sizes. The results show that the most time lagging comes from image files, followed by PDF files, and then text files Moreover the encryption and decryption process using the modified system is around twice faster than the old system.